Factors contribute to customer complaint towards services at operation department in Johor Port Berhad / Aqashah Shahren Luqman - Luqman, Aqashah Shahren (Faculty of Business and Management, 2013)
Port is one of the important links between different modes of transport within the logistics chain. In other words, ports play a vital role for the purpose of achieving more customers in the international market. Customer is the people who bring a profit to the ports. However, the local port exists in Malaysia such Johor Port is burdened with customer complaint where the problems that keep arise in operation department when they use the services. The aim of this paper is focus on the factor that contributes to customer complaint towards services at operation department in Johor Port Berhad. The researchers use three variables which consist of congestion, warehouse and quay.